Makna susu bagi konsumen mahasiswa di kafe susu di Yogyakarta: antara gizi dan gengsi - Atik Triratnawati (Jurnal Gizi Klinik Indonesia, 2017)
Background: The rise of milk cafe in Yogyakarta with visitors of student raises a question mark what purpose they consume milk. There is definitely an attraction that encourages students are willing to spend time, effort, and expenses for the sake of enjoying a glass of milk that can actually be done at home.Objective: To find the meaning of intrinsic and extrinsic of students consumer milk cafe in Yogyakarta.Method: This was a qualitative study using observation and in-depth interview with student consumer at milk cafe in DIY.Results: A new lifestyle among students appearing through hanging out in cafes milk for the purpose of the task, sharing, refreshing. Visitors cafes in addition to experience the benefits of drinking milk fresh milk with a variety of flavors, so the fishy taste is lost and replaced various delicious new taste sensation. They are also regarded as a milk cafe hangout for young slang. Place milk cozy cafe, with music, attractive interior, wifi facility on site to make it become a means for a selfie and comfortable group meetings.Conclusion: Nutrition of milk was not important things for them. Prestige then attached to the visitor’s cafe milk given modern attributes and symbols attached to their lifestyle. The symbolic meaning of milk consumption in cafe milk is stronger than the natural sign, so the students are still high in demand for cafe milk.